Custo de produção e rentabilidade de abacaxizeiro cv. pérola em cassilândia (ms), sob diferentes doses de potássio - dos Reis, Luis Lessi [UNESP] (2012)
The pineapple crop are high potential for economic expression and social, but problems with productivity and management of production costs can be solved in order to ensure the sustainability of the farming system. The objective of this study was determine the cost of production and profitability of the pineapple's cultivation Pearl in Cassilândia-MS, under application of potassium doses fertilizer. The treatments consisted of the following doses of potassium (K2O): 0, 200, 400, 600, 800 kg ha-1, used as a commercial source of potassium chloride (60% K2O). Were determined by estimating the effective operational cost (EOC), total operating cost (TOC), gross (RB), operating profitability (LO), profitability index (%), productivity of balance and equilibrium price. It was found that all treatments had operating profitability and positive profitability index. Potassium fertilization with 200 kg ha-1 gave an average productivity of 50416.58 kg ha-1, and also promoted the highest operating profit of R$ 9,108.97, the profit margin of 36.13% and best benefit cost (R$ 1.57).